Anomalous Lattice Dynamics in AgC4N3: Insights From Inelastic Neutron Scattering and Density Functional Calculations - Singh, Baltej; Gupta, Mayanak K.; Mittal, Ranjan; Zbiri, Mohamed; Hodgson, Sarah A.; Goodwin, Andrew L.; Schober, Helmut; Chaplot, Samrath L. (Frontiers in Chemistry, 2018)
We have performed temperature dependent inelastic neutron scattering measurements to study the anharmonicity of phonon spectra of AgC4N3. The analysis and interpretation of the experimental spectra is done using ab-initio lattice dynamics calculations. The calculated phonon spectrum over the entire Brillion zone is used to derive linear thermal expansion coefficients. The effect of van der Waals interaction on structure stability has been investigated using advanced density functional methods. The calculated isothermal equation of states implies a negative linear compressibility along the c-axis of the crystal, which also leads to a negative thermal expansion along this direction. The role of elastic properties inducing the observed anomalous lattice behaviour is discussed.